Assessment of dermal absorption of beryllium and copper contained in temple tips of eyeglasses. (15th May 2022) - Magnano, Greta Camilla; Marussi, Giovanna; Adami, Gianpiero; Crosera, Matteo; Larese Filon, Francesca
Abstract: Dermal exposure to hazardous substances such as chemicals, toxics, metallic items and other contaminants may present substantial danger for health. Beryllium (Be) is a hazardous metal, especially when inhaled and/or in direct contact with the skin, associated with chronic beryllium disease (CBD) and Be sensitization (BeS). The objective of this study was to investigate the percutaneous penetration of beryllium and copper contained in metallic items as eyeglass temple tips (specifically BrushCAST® Copper Beryllium Casting Alloys containing Be 0.35 < 2.85%; Cu 95.3–98.7%), using Franz diffusion cells. This work demonstrated that the total skin absorption of Cu was higher (8.86%) compared to Be (4.89%), which was expected based on the high percentage of Cu contained in the eyeglass temple tips. However, Be accumulated significantly in the epidermis and dermis (up to 0.461 µg/cm 2 ) and, to a lesser extent, in the stratum corneum (up to 0.130 µg/cm 2 ) with a flux of permeation of 3.52 ± 4.5 µg/cm 2 /hour and lag time of 2.3 ± 1.3 h, after cutaneous exposure of temple tip into 1.0 mL artificial sweat for 24 h. Our study highlights the importance of avoiding the use of Be alloys in items following long-term skin contact. Graphical Abstract: ga1 Highlights: Skin may be a route of entry of metals after contact with metallic items. Dermal absorption of Beryllium (Be) and Copper (Cu) may cause skin sensitization and toxicity in humans. After the deposition of eyeglass temple tips on the skin, Be and Cu can penetrate and permeate this cutaneous membrane. Pig skin is a suitable in vitro experimental model for human skin.